From the Neolithic to the end of Early Bronze Age: developments in the construction of entrance gates and city walls at settlements in Burdur (Turkey) and the surrounding region - Gülsün Umurtak (Българско е-Списание за Археология)
The excavations at Hacılar carried out by James Mellaart in Burdur in the second half of the 1950s were a starting point for prehistoric archaeology in the Burdur–Antalya Region (Ancient Pisidia). Almost two decades later excavations took place at Kuruçay Höyük (1978–1988), followed by excavations at the Hacılar necropolis (1985-1986), excavations at Höyücek (1989–1992) and Bademağacı Höyük (1993–2010), and excavations at Hacılar Büyük Höyük that began in 2011 and are still in progress. The first examples of fortified settlements in the region can be traced back to the Early Neolithic Period. The centres mentioned in this article represent very significant stages in both the development of defence architecture in the region and also in our understanding of the process of urbanisation in Anatolia. The earliest defence models were later replaced by more complex systems, such as the casemate and saw-tooth defence system seen in the EBA I settlement at Hacılar Büyük Höyük, and the arrangement of adjacent megarons in a row for the purpose of defence in the EBA II settlement at Bademağacı. The first example of a ‘Gate Building’ model in Anatolia is the Eastern Gate in level 6A at Kuruçay, which consists of a gateway between two casemates/ towers. The development of this type of gate can be seen in the Western Gate and the Southern Gate at Hacılar Büyük Höyük.